Analisis Tingkat Aksesibilitas Halaman Utama Situs Web Perguruan Tinggi Di Indonesia Berdasarkan WCAG 2.0 - Mayda Arofata Frandini; Ismiarta Aknuranda; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Universities are one of the educational institutions that provide inclusive education for people with disabilities. Universities use the website as a medium of information dissemination. An important part of a website is homepage, which contains and reflects the entire website content information. Web accessibility means that everyone is able to use the website properly without any obstacles from a person's physical limitations. One of the standards governing web accessibility is Web Content Accessibility Guidelines 2.0 (WCAG 2.0). But until now in Indonesia there is no information about the level of accessibility of the website, especially on the homepage of the universities website and what issues reduce its accessibility. This research is analytical which evaluate the homepage of universities website in Indonesia. Evaluation is done with the help of AChecker and WAVE evaluation tool. The evaluation results will categorize the college website's homepage into accessible, partially accessible and inaccessible categories. WABS calculations are used to determine the ranking of the impact of problems that affect the decrease in web accessibility, so that recommendations can be given to improve accessibility of the college website's main page. This study shows that 23.9% of universities website are inaccessible. Very low contrast and errors in the use of alternative text on the site to be the majority of problems that require improvement